(3fgGjI GdeWdH aj OQGjI GdePgHs - (3YHO Gdedc Hf YHO Gddg Hf jhSa Hf eMeO GdLhjfj, CHh GdeYGdj, Qcf GdOjf, GdedbH HEeGe GdMQejf,J (B478 (3g` s
(3ChdgG (B:s
(3Chdg eHJhQ , hjHOC GdehLhO efg CKfGA GdcdGe Ydi (B" (3GdYGQjI (B" (3Hbhdg (B: (3dCfG bjOfG GdcdGe HGdeGd , habgg Cf GdeGd dg HOd , hCecf JVejf HOdg s
(3BNQgG (B:s
(3jfJgi HBNQ cJGH GdeSGbGg , hBNQ eG ajg (B: (3hdh cGf Gdfjd eWYhekG aCHGM def jCcdg Ch jTQHg , aeG LQi ef Pdc adG eYJQV ajg , hdG VeGf hGddg CYde BNQ GdeLdO GdKGef s
(3HBNQgG ebGHdI SfI (B674(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B160s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdESdGejs